2015
DOI: 10.1108/ijcoma-03-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between total quality management practices and their effects on bank’s technical efficiency

Abstract: Purpose -The purpose of this paper is to investigate the relationship between total quality management (TQM) practices and banks' technical efficiency. Design/methodology/approach -A survey questionnaire was constructed to measure TQM practices and quantitative data were collected to measure banks' technical efficiency. The respondents were required to indicate their degree of implementation of quality management practices in the survey instrument. Organizational performance was indicated by quantitatively mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The conceptual model of the study illustrated in Figure 2 the dimensions of TQM practices were adopted from the following studies: Cha (2019), Salhieh and Abu-Doleh (2015), Wu (2015), Shan et al (2013), Talib et al (2013), Zwain (2012), Ismail Ababaneh (2010), Zeng et al (2007) and Lakhal et al (2006). Leadership and management commitment; customer focus; people management; strategic planning; processes management; rewards and recognition; and employee involvement all acted as the independent variables.…”
Section: Problem Statementmentioning
confidence: 99%
“…The conceptual model of the study illustrated in Figure 2 the dimensions of TQM practices were adopted from the following studies: Cha (2019), Salhieh and Abu-Doleh (2015), Wu (2015), Shan et al (2013), Talib et al (2013), Zwain (2012), Ismail Ababaneh (2010), Zeng et al (2007) and Lakhal et al (2006). Leadership and management commitment; customer focus; people management; strategic planning; processes management; rewards and recognition; and employee involvement all acted as the independent variables.…”
Section: Problem Statementmentioning
confidence: 99%
“…Regarding the assessment of the bank's technical efficiency based on DEA, generally, two distinctive approaches, the production approach and the intermediation approach, were adopted for assessing the relative efficiency of banking (Avkiran, 2011). In the current study, following Shahwan and Hassan (2013) and Salhieh and Abu-Doleh (2015), the production approach was adopted. Consequently, three input variables, namely, total expenses, customer deposits and fixed assets, were adopted, while two variables, total income and net cash from operating were used as output variables.…”
Section: Methodsmentioning
confidence: 99%
“…Kuah and Wong [23] applied a two-level DEA model for measuring the performance of Malaysian universities with regard to KM factors while Shirouyehzad et al [24] considered the criteria of KM and safety management as inputs and customer satisfaction and accident indicators as outputs of a DEA model for performance evaluation of 12 companies in the car industry in Esfahan. In addition, Salhieh and Abu-Doleh [25] indicated the impact of TQM on banks efficiency applying a DEA-based approach. However, some research can be found which applied DEA for selecting, improving, or evaluating six sigma projects as well.…”
Section: Literature Reviewmentioning
confidence: 99%